Sztylet krzemienny typu skandynawskiego z Charzykowych. gm. Chojnice - Wojciechowski, Włodzimierz (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
Flint daggers with attributes reminiscent of late Neolithic Scandinavian forms are relatively numerous in western Poland, notably in Pomerania where, however, their distribution is uneven. A distinct concentration of these objects is noted in western Pomerania while in its eastern part they occur only in a narrow zone along the Baltic coast, bounded in the south by the high, central Pomeranian moraine. No finds of this type have been recorded in south-eastern Pomerania within the Brda, Wda and Wieżyca basins, i.e. west of the lower Vistula. The dagger in question, representing the earliest type (I) in this category of flint artifacts, is an accidental stray find turned up by ploughing (a detailed survey of the surrounding area failed to reveal any remains of a grave). It comes from the central part of this area so far sterile of these finds and suggests that their original distribution may have been much more even. This concerns particularly the typologically earliest forms, single examples of which have been revealed earlier in the southern part of central Pomerania at the confluence of the Gwda and Noteć rivers. In Pomerania, flint daggers of type I should be linked with the early phase of the Grobia-Śmiardowo culture dated to Bronze Age I. For this reason the dagger from Charzykowy has a particular significance as it provides evidence for the penetration of eastern Pomerania by the people ot that culture at the beginning of the Early Bronze Age (early phase of the Grobia-Śmiardowo culture). So far Early Bronze Age finds, rather scarce in the region in question (more numerous finds on the left bank of the lower Vistula are an exception) have indicated the presence of the representatives of only the later part of that period (later phase of the Grobia-Śmiardowo culture coeval with the classic phase of the Únčtice culture). The dagger in question allows us to expect further finds of this type in eastern Pomerania, perhaps in the context of so-called tub-like graves typical of the Grobia-Śmiardowo culture.